Gambaran Pemberian Terapi Acbt dan Latihan Batuk Efektif Terhadap Frekuensi Pernapasan, Spo2 Modified Skala Borg Pada Anak Dengan Bronkitis Akut di Ruangan Ibnu Sina: Case Report - Mar’atun Shalihah; Rahmah Rahmah; Irni Mastiarini (Universitas Pahlawan Tuanku Tambusai, 2026)
Acute bronchitis is one of the respiratory tract diseases that often occur in children and is characterized by the main symptoms in the form of coughing, both dry and phlegm. This condition can cause a buildup of secretions in the airways so that it interferes with airway cleaning and has the potential to cause shortness of breath and decreased oxygenation status if not handled properly. One of the efforts made is that ACBT and cough are effective to improve ventilation and help secretion through breathing control, deep breathing, and huffing as well as maintaining the patency of the respiratory tract. This study aims to provide an overview of the application of Active Cycle of Breathing Technique therapy and effective cough exercises on oxygenation status, respiratory frequency, and respiratory shortness of breath in children with acute bronchitis. The research method uses case reports with Single-Case Experimental Design (SCED) design through O1 and O2 designs. The subject is a child with acute bronchitis. Active Cycle of Breathing Technique interventions and effective cough exercises were administered three times a day for four days, with pre- and post-action monitoring to assess the patient's response. The monitoring results showed that after the intervention was given, the level of tightness remained in the minimum category, the respiratory frequency was in the normal range according to the child's age, and there was an increase in oxygenation status compared to pre-intervention conditions. Conclusion: The application of Active Cycle of Breathing Technique and coughing exercises effectively has a positive impact on airway hygiene and supports the recovery of respiratory conditions in children with acute bronchitis.